2019
DOI: 10.1371/journal.pone.0211186
|View full text |Cite
|
Sign up to set email alerts
|

Axial length and its associations in a Russian population: The Ural Eye and Medical Study

Abstract: PurposeTo assess the normal distribution of axial length and its associations in a population of Russia.MethodsThe population-based Ural Eye and Medical Study included 5,899 (80.5%) individuals out of 7328 eligible individuals aged 40+ years. The participants underwent an ocular and systemic examination. Axial length was measured sonographically (Ultra-compact A/B/P ultrasound system, Quantel Medical, Cournon d'Auvergne, France).ResultsBiometric data were available for 5707 (96.7%) individuals with a mean age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
24
3
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 39 publications
(44 reference statements)
7
24
3
2
Order By: Relevance
“…However, these differences are typically small and are not significant in other studies when combined with further systemic parameters in multiple regressions. 36,37 Moreover, ocular magnification is a combination of axial length and lens-related effects, and several previous population-based studies showed significantly higher rates of myopia in females. [38][39][40][41][42][43] Based on this, and contrary to the expectations based on axial length noted previously, one alternatively might assume that females harbor larger ocular magnification (i.e., larger scanning radius) compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…However, these differences are typically small and are not significant in other studies when combined with further systemic parameters in multiple regressions. 36,37 Moreover, ocular magnification is a combination of axial length and lens-related effects, and several previous population-based studies showed significantly higher rates of myopia in females. [38][39][40][41][42][43] Based on this, and contrary to the expectations based on axial length noted previously, one alternatively might assume that females harbor larger ocular magnification (i.e., larger scanning radius) compared with males.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted the Ural Eye and Medical Study, designed as a population-based, case-control investigation, in the Russian republic of Bashkortostan at the southwestern end of the Ural Mountains from October 26, 2015, to July 4, 2017. [9][10][11] The inclusion criteria were age 40 years or older and living in 1 of the 2 study regions: the urban region of Kirovskii in the city of Ufa, the capital of the republic, or a rural region in the Karmaskalinsky District, which is 65 km from Ufa. Of 7328 eligible individuals, 5899 individuals (80.5%) with a mean (SD) age of 59.0 (10.7) years (range, 40-94 years) participated in the survey.…”
Section: Methodsmentioning
confidence: 99%
“…Several population-based studies suggested that AL played a different role in DR genesis and development in different ethnicities, although some contradictory results existed in literature. 79 A recent cohort study of Singaporean population demonstrated that the any DR risk decreased by 42% for each 1 mm increase. However, the aforementioned study reported no correlation of AL with the risk of VTDR.…”
Section: Discussionmentioning
confidence: 99%
“…3 It was found however in clinical practice that diabetic patients with myopia are less likely to suffer from severe DR. 4 A small number of clinical studies and epidemiological studies have suggested that myopia could be a protective factor against DR; however, this conclusion remains controversial. 47…”
Section: Introductionmentioning
confidence: 99%